Analisis Hukum Islam terhadap Praktik Nikah Tahlil - Aulia Diningrum; Naziroh Naziroh; Putri Dahlia Hasibuan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Tahlil marriage is a marriage carried out with the aim that a woman who has been divorced three times by her husband can remarry her first husband after marrying and divorcing her second husband. This is a matter of debate in Islamic law, especially from the perspective of the four main schools of thought: Hanafi, Maliki, Shafi'i, and Hambali. This research aims to analyze tahlil marriage law according to the views of the four schools of thought using a normative approach. The research method used is library research by examining classical and contemporary jurisprudence books as well as the opinions of ulama.The results of the research show that the majority of ulama from four schools of thought agree that if a tahlil marriage is carried out with conditions and an initial agreement to divorce after the contract, then the marriage is considered void or haram because it violates the principles of marriage in Islam. However, if the marriage occurs without a prior agreement to divorce, then the law is valid. The conclusion of this research confirms that the deliberate and planned practice of tahlil marriage is contrary to the principle of the validity of marriage in Islam. Therefore, it is important for Muslims to understand marriage laws in accordance with Islamic teachings so as not to be trapped in practices that are not valid according to sharia.